JSPS-CAS core University Program Seminar on Summary of 10-year Collaborations in Plasma and Nuclear Fusion Research Area - JSPS-CAS core University Program Seminar on Summary of 10-year Collaborations in Plasma and Nuclear Fusion Research Area (2011 : Okinawa, Japan); Toi, Kazuo, editor; Wang, Kongjia, editor; National Institute for Fusion Science (Toki, Japan : National Institute for Fusion Science, 2011)
PSZJBL